Concern for Pain in the Pre‐Operative Period‐ Is the Internet Being Used for Information By Patients?. Issue 2 (22nd May 2013) - Kurup, Viji; Dabu‐Bondoc, Susan; Senior, Audrey; Dai, Feng; Hersey, Denise; Vadivelu, Nalini
Abstract Objectives This study was conducted to provide information regarding prevalence of pain, type of provider managing pain, and use of Internet for information regarding pain, among patients coming for presurgical anesthesia consultation at a major academic institution. Methods With IRB approval, patients were invited to participate in a voluntary and anonymous 14 question survey given to them when they presented for anesthesia consultation prior to their surgical procedure. The qualitative/categorical data were summarized by number (percentage [%]) and analyzed by Chi‐square test or Fisher's exact test as appropriate. All data analyses were performed using the statistical software SAS, v9.2. Results A total of 1039 patients were asked to complete the survey and 670 patients returned their responses (response rate = 64.5%). 83% of patients had a history of prior surgery. 57% were concerned about postoperative pain. 30% of patients had chronic pain for more than 3 months pre‐operatively. 16% of patients had looked online for information regarding pain. Pain physicians were involved in pain management only in 3.8% of these patients. Discussion Patients are presenting for surgery with significant pre‐operative pain issues. Knowing this information pre‐operatively will help healthcare personnel manage postsurgical pain more effectively. Patients are also using the Internet to obtain information regarding pain. As providers, there may be value to directing patients to reliable information online during consultation. As all physicians will eventually be managing chronic pain in their patients, pain education should be given priority in medical school curriculum.